METODE CERAMAH MENJADI SALAH SATU PENYEBAB RIBUTNYA PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS 1 SDN 026 ROKAN - Ervina Julyanita; Dwi Hijriani, Adrias Adrias, Fadila Suciana (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The lecture method is one of the approaches often used by educators in delivering learning materials, especially in the context of Pancasila learning. In this method, educators convey information directly to students, so that they can understand the concepts taught. This study aims to explore the effectiveness of the lecture method in Pancasila learning. To achieve this goal, the researcher applied a qualitative approach, which allows for in-depth and comprehensive data collection. The researcher conducted interviews with class teachers to obtain their perspectives on the use of the lecture method that had been used. In addition, the researcher also analyzed the values obtained by students during the learning process. In this way, it is hoped that a clear picture can be obtained regarding the impact of the lecture method on students' understanding and achievement in the Pancasila subject. The results of this study are expected to contribute to the development of more effective teaching methods in the future.